Eksistensi Gamelan Amak Aber di Desa Mendane Raya Kecamatan Keruak Kabupaten Lombok Timur - Azizah, Naila Yusri (TAMUMATRA, 2019)
This study aims to describe the existence of Gamelan AmakAber at Mendae Raya Village, KeruakSub-district, and EastLombok Regency. This art has the important role to play, this study focused on the existence and function of Gamelan AmakAber. This study used a qualitative descriptive method. The subject of this study was Gamelan AberAber. The data collection technique used in this study was interview, observation and documentation. The validity check of the data in this study used source triangulation. The data analysis technique used consist of four stages, namely, data collection (data collection), reduction (data reduction), display data (data presentation), and conclusions drawing / verification (conclusion examiner and verification). The result of this study included the existence of AmakAber gamelan in detail. The art of Gamelan AberAmak was first brought to Mendane Raya in 1920 by DatukDaiman. Gamelan AmakAber art that does not allow woman to play in this art is very sacred. The preservation of Gamelan AmakAber art is carried out by always maintaining the authenticity of the art and recruiting young player or friend. This art function is entertainment, nyongkolan, khitanan, village peririk and source of livelihood.